2011
DOI: 10.1371/journal.pone.0021347
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Oxidative Phosphorylation Compensation May Preserve Vision in Patients with OPA1-Linked Autosomal Dominant Optic Atrophy

Abstract: Autosomal Dominant Optic Atrophy (ADOA) is the most common inherited optic atrophy where vision impairment results from specific loss of retinal ganglion cells of the optic nerve. Around 60% of ADOA cases are linked to mutations in the OPA1 gene. OPA1 is a fission-fusion protein involved in mitochondrial inner membrane remodelling. ADOA presents with marked variation in clinical phenotype and varying degrees of vision loss, even among siblings carrying identical mutations in OPA1. To determine whether the degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 70 publications
0
40
0
Order By: Relevance
“…Therefore, a reduction in OPA1 directly affects mitochondrial respiration via a reduction in the oxidative phosphorylation process [36]. In the obese insulin-resistant rats with testosterone deprivation, OPA1 protein levels were reduced along with a reduction in mitochondrial respiratory complexes I and III.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a reduction in OPA1 directly affects mitochondrial respiration via a reduction in the oxidative phosphorylation process [36]. In the obese insulin-resistant rats with testosterone deprivation, OPA1 protein levels were reduced along with a reduction in mitochondrial respiratory complexes I and III.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestation of OPA1 mutations is often highly variable between siblings. 48 Experimental knockdown of OPA1 performed by different tools and laboratories resulted in highly variable phenotypes (see above). Ca 2 þ handling is not an exception from this.…”
Section: Discussionmentioning
confidence: 99%
“…54 Based on our data, mitochondrial Ca 2 þ load is likely to be reduced in OPA1-deficient RGCs, and therefore the aggravation of DCD that was observed is possibly due to the decreased respiratory capacity. Along this line, DOA patients with higher respiratory complex activities have been reported to maintain visual acuity for a longer period of time, 48 again suggesting that the bioenergetic compromise may be at the root of RGC damage. Because RGC mitochondria do not show any abnormalities in protein expression, the focus should turn to RGC idiosyncrasies in terms of mitochondrial energy metabolism and environmental stress factors.…”
mentioning
confidence: 90%
“…42,43 It has been reported that poor visual acuity in ADOA patients is associated with mutations in the OPA1 gene, which result in defective OXPHOS capacity of the mitochondria. 44 Mutations in OPA1 lead to disruption of mtDNA structure, replication, and transcription, ultimately affecting OXPHOS capacity.…”
Section: Optic Neuropathies: Mitochondrial Involvementmentioning
confidence: 99%